Buildings for Bodies of Work: The Artist Museum After the Death and Return of the Author. Issue 1 (12th June 2019) - Liefooghe, Maarten
Abstract : Critiques of the cult of artists, life-and-work narratives, and the authority of authors over the meaning of their works not only unsettle the conventions of literary and art historical studies. They also challenge the importance of the artist museum and its architecture. Adopting Roland Barthes' discussions of the 'death' and 'return of the author' of the late 1960s and early 1970s as a critical lens, this article examines how the architecture of artist museums reflects and contributes to the discursive construction of the resilient figure of the artist-author. To do so, the article compares the cultist make-up of the 19th-century Thorvaldsen Museum-Mausoleum (opened in 1848) with the resolutely work-centred museums of Van Gogh (1973) and Roger Raveel (1999). The architecture of the last two examples is significantly different, however. The Van Gogh Museum seemingly negates its monographic orientation, while the Raveel Museum amends a white cube logic with a reserved interpretation of artistic individuality and site-boundedness. Parallel to the institutional interpretation of a museum's monographic mission, and the curators' representation of the artist-life-work nexus in exhibitions, architecture is yet another element in a museum's assemblage of an artist presented as a dead or revived author to its visitors.